A comparative study of tax incentives for small businesses and investors in small businesses in South Africa, Australia, New Zealand, Singapore and Ireland - Horn, Edward Bennet (Rhodes University, Faculty of Commerce, Department of Accounting, 2018)
In the South African context, it is accepted that small businesses will be the vehicle for job creation and changing the current business ownership patterns. This is to be achieved by creating access to finance, exploring the role of venture capital and simplifying the tax obligations and the compliance burden. The literature indicates that the current South African tax incentives for small businesses are perceived as unfair and fundamentally ineffective. The objective of this thesis was to compare the tax incentives available to small businesses and investors in small businesses in South Africa to those available in Australia, New Zealand, Singapore and Ireland, in order to identify possible measures that could be introduced in South Africa. In addressing the objective, the research set out to provide, in terms of South African tax legislation, a definition of a small business for tax purposes and document the tax incentives available for start-up and existing small businesses, as well as the tax incentives available for investors in small businesses, either through a venture capital company or a direct investment in small business. It was found that South Africa has a complex and onerous multi-layered approach to classifying a taxpayer as either a "micro business" or a "small business corporation" for the purpose of applying tax incentives. The international jurisdictions included in this research follow a single requirement approach, based on either one or a combination of turnover, balance sheet total or staff headcount. The international jurisdictions provide a wide range of tax incentives to small businesses and investors in small businesses, aimed at reducing taxable income to enable the small businesses to grow and access equity finance. By identifying differences and similarities, a number of possible tax relief measures were recommended that could be introduced in South Africa.
Keywords: Small business -- Taxation -- South Africa; Small business -- South Africa -- Finance; Job creation -- South Africa; Government aid to small business -- South Africa; Tax incentives -- South Africa; Tax incentives -- Australia; Tax incentives -- New Zealand; Tax incentives -- Singapore; Tax incentives -- Ireland